A novel dance intervention program for children and adolescents with developmental disabilities: a pilot randomized control trial - Jeffrey T. Anderson; Christina Toolan; Emily Coker; Hannah Singer; Derek Pham; Nicholas Jackson; Catherine Lord; Rujuta B. Wilson (BMC, 2024)
Abstract Background Organized physical activity programs have been shown to provide wide benefits to participants, though there are relatively few studies examining the impact of these programs for individuals with developmental disabilities. This pilot study was conducted to determine the feasibility and impact of an undergraduate-led dance intervention program for children and adolescents with developmental disabilities. We evaluated the impact of the dance program on motor ability and social skills. Methods The study design was a waitlist control clinical trial in which participants were randomized to active and control groups. Eligible participants included male and female children and adolescents between the ages of 4 and 17 years with neurodevelopmental disabilities. The Motor Assessment Battery for Children Checklist and the Social Responsiveness Scale were used to assess change in motor and social skills, respectively. After gathering baseline data, the active group completed 1 h of online dance classes per week for 10 weeks, while the control group entered a 10-week waiting period. All participants then returned for a follow-up visit. Pre- and post-intervention data were analyzed using linear mixed-effects modeling adjusting for age and class attendance with subject random intercept. Results We recruited and randomized 43 participants with neurodevelopmental disabilities (mean age = 8.63, SD = 2.98), of which 30 participated in dance classes. The attendance rate was 82.6% for the active group and 61.7% for the control group. The active group demonstrated a significant improvement in motor skills in an unpredictable environment, as indicated on the Motor Assessment Battery for Children Checklist (n = 21, p = 0.05). We also observed positive trends in social skills that did not reach significance. Conclusions Our results indicate that it is feasible to develop and implement a fully digital dance intervention program for individuals with developmental disabilities. Further, we find that change in motor skills can be detected after just 10 h of low-intensity participation. However, a lack of significant change in social skills coupled with limitations in study implementation suggests further research is needed to determine the full impact of this dance program. Trial Registration ClinicalTrials.gov Protocol Registration System: Protocol ID 20-001680-AM-00005, registered 17/2/2021 - Retrospectively Registered, https://clinicaltrials.gov/study/NCT04762290 .